Análise de conceito do diagnóstico de enfermagem controle ineficaz da saúde em pessoas vivendo com Aids - Santos, Wenysson Noleto dos (2018)
This is a concept analysis, according to the Walker and Avant method, operationalized through integrative review, aiming to analyze the concept of nursing diagnosis ineffective control of health in people living with AIDS. To do so, we searched the databases: Scopus, Cinahl, PubMed, Web of Science, Science Direct, Cochrane and Lilacs, using the descriptors: Cooperation and Adherence to Treatment; adherence to medication and acquired immunodeficiency syndrome. Data collection was performed between January and March 2018, by the researcher. The initial sample was 7693 articles, 1,029 in Scopus, 427 in CINAHL, 3,673 in PubMed, 1,280 in the Web of Science, 646 in Science Direct, 354 in Cochrane and 284 in LILACS. Next, the inclusion criteria were applied to refine the search, ie: articles available in the selected databases in Portuguese, English or Spanish; studies that respond to the proposed guiding questions. The following exclusion criteria were applied: prior notice, protocols, ongoing research, reviews, editorials and letters to the editor. After the application of the established criteria, a final sample of 46 articles was obtained, 14 in Scopus, 3 in Cinahl, 8 in PubMed, 6 in Web of Science, 5 Science in Direct, 7 in Cochrane and 3 in Lilacs. Five attributes, 34 antecedents and 17 consequent ones were identified. The concept was defined as: a dynamic and multifactorial process that involves physical, psychological, behavioral, socio-cultural, environmental and economic aspects related to the difficulty of following the therapeutic plan agreed between the person / caregiver and the health professional, negatively affecting their condition clinical and quality of life; and bringing personal, social and economic consequences to people living with AIDS. Thus, the definition of NANDA International for the diagnosis Ineffective control of health and its components need a complementation, aiming at a better targeting of care to people living with AIDS. It is possible to infer that it is necessary to carry out other studies on the subject. It is hoped to carry out future research to carry out content validation and clinical validation of the concept of ineffective health control in people living with AIDS. Finally, this study has the potential to advance the literature on the subject by synthesizing, defining and analyzing the phenomenon of ineffective health control in people living with AIDS.